Analysis of Symbolic Geography of Cavern-Space in Ruzbihan’s Exegesis, Arais-al-Bayan: A Thematic Critical Approach - Razieh Hojjatizadeh (ادبیات عرفانی, 2016)
One aspect of Qur’anic influence on mystical exegeses is its attention to temporal and spatial dimensions of human life. Various critical theories of contemporary literary criticism deal with spatial analysis; among which Horizon-Paysage theory of Michel Collot is considered appropriate for analyzing Ruzbihan’s exegesis. As a branch of thematic critical approach, this theory transforms space from a background element in narratives to a symbolic and significant one and elucidates mystical worldview through interactions between human and environment. In view of that, this paper seeks to explore the relationship between cavern space and mystical vision of Ruzbihan in Arais-al-Bayan. In brief, it seems that Ruzbihan has adopted a phenomenological approach to space issue. Cavern is symbol of an eternal reminiscence that a mystic strives to display in his journey in form of several frames of revelations. In describing such frames, the mystic does not stay in one space and keeps crossing different ones.  He moves from cavern of body to cavern of observance, and then to cavern of zeal, soul, affection, and the like. Hence, in mystical experience, space is not an enclosed, impassable reality but a malleable one which accompanies the mystic on his journey of evolution.